2015
DOI: 10.1007/s11255-015-1055-4
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of guideline targets in elderly patients on hemodialysis: a multicenter study

Abstract: Despite less favorable dialysis prescription, older patients had similar Kt/V and less frequent deviations from the target values proposed by KDOQI for serum phosphorus and iPTH but more frequent deviation for Hb value as compared with younger patients. Risk factors for mortality differ between older and younger patients; out of five KDOQI targets, only Kt/V proved to be a significant risk factor for mortality for younger and iPTH for older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The causes of ESRD, comorbidity, and risk factors for mortality differ between older and younger patients. 15 Older patients exhibited lower serum P, iPTH, and albumin levels and reduced protein intake compared with younger patients undergoing hemodialysis. 9 , 15 Results from previous studies supported the significant association between the markers of MBD and risks of both cardiovascular and all-cause death; however, cardiovascular deaths accounted for approximately 50% of the total deaths in the study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The causes of ESRD, comorbidity, and risk factors for mortality differ between older and younger patients. 15 Older patients exhibited lower serum P, iPTH, and albumin levels and reduced protein intake compared with younger patients undergoing hemodialysis. 9 , 15 Results from previous studies supported the significant association between the markers of MBD and risks of both cardiovascular and all-cause death; however, cardiovascular deaths accounted for approximately 50% of the total deaths in the study.…”
Section: Discussionmentioning
confidence: 93%
“… 15 Older patients exhibited lower serum P, iPTH, and albumin levels and reduced protein intake compared with younger patients undergoing hemodialysis. 9 , 15 Results from previous studies supported the significant association between the markers of MBD and risks of both cardiovascular and all-cause death; however, cardiovascular deaths accounted for approximately 50% of the total deaths in the study. 3 , 16 Our study showed that cardiovascular death accounts for approximately one-third (36.8%) of total deaths in older patients undergoing MHD.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, HD patients from Serbia were younger than those from Western Europe. This difference may influence achievement of guideline targets, as already mentioned [23]. …”
Section: Discussionmentioning
confidence: 98%
“… 8 In addition, advanced age is associated with shorter survival in patients undergoing MHD. 9 Older patients are more likely to die of their primary disease when initiating dialysis and they are also more likely to experience various complications of dialysis. 10 Previous studies have also shown that advanced age and long-term dialysis are associated with the progression of MHD in patients.…”
Section: Introductionmentioning
confidence: 99%